The Changing Digital Culture and its Impact on Women - Sharma, Sunita Ramesh (Lingual Journal of Language and Culture, 2020)
Information and Communication Technologies (ICTs), including the Internet, are increasingly influential across all aspects of life. Women’s Equality is one of the 17 Sustainable Development Goals, but also integral to all dimensions of Inclusive and Sustainable Development. E-Commerce also known as internet commerce, refers to the buying and selling of goods and services using the internet. The companies of the future, through the rules of electronic commerce, form a new productive framework. These digital transformations have managed to generate new labour paradigms. The paper lists the new jobs profile created by technology. It attempts to find answers to, whether the women are going to benefit from the changes that take place in the labour market and in the economy in general? And is there a new window of opportunity? Or is it simply more of the same? It concludes by giving suggestions, so that the ladder of women development is not thrown away. Keywords: Internet and gender, Labour paradigms, Algorithms and gender.